Revolution 2.0 : the power of the people is greater than the people in power : a memoir - Ghonim, Wael, 1980- (Boston : Houghton Mifflin Harcourt, 2012)
A key figure behind the Egyptian uprising in January 2011 which resulted in the ousting of President Mubarak tells the inside story and presents lessons on how to unleash the power of crowds to create political change.
A regime of fear -- Searching for a savior -- "Kullena Khaled Said" -- Online and on the streets -- A pre-announced revolution! -- January 25, 2011 -- My name is 41 -- The dungeon -- A pahraoh falls..
Includes index.
Keywords: Ghonim, Wael, -- 1980-; Political activists -- Egypt; Internet -- Political aspects -- Egypt; Egypt -- History -- 1981-; Ghonim, Wael, -- 1980-; Political activists -- Egypt -- Biography; Internet -- Political aspects; Egypt -- History